The ideal and the counter-ideal follower – advancing implicit followership theories. Issue 8 (7th November 2016) - Junker, Nina M.; Stegmann, Sebastian; Braun, Stephan; Van Dick, Rolf
Abstract : Purpose: Research on implicit followership theories – that is, individually held assumptions about how followers are and how they should be – is still in its infancy. The few existing approaches differ in what they define as the object of these theories. The authors consider the lack of two aspects in the existing literature: first, the authors consider it important to not only focus on effective but also on ideal followers – which allows investigating follower characteristics that go beyond just performance; and second, the authors demonstrate the importance of the study of characteristics which leaders explicitly see as undesirable for followers (i.e. counter-ideal follower prototypes). The purpose of this paper is to fill these gaps and to extend the literature by introducing the concept of implicit followership theories as assumptions of ideal followers. Design/methodology/approach: The authors first present three studies conducted to develop a scale to measure ideal and counter-ideal follower prototypes, respectively. In a fourth study, the authors apply this scale and compare it to existing measures of implicit followership theories regarding their value for predicting leaders' follower ratings. Findings: Results show that the newly developed measure is reliable and valid, and comprises a useful tool for future research. Practical implications: The scale can be used for leadership development programs. Originality/value: The study is among the few that provide theory and evidence for the relevance of implicit followership theories and is the first to consider the ideal follower in this regard.